Digital Health and Health Systems of the Future - Labrique, Alain (Glob Health Sci Pract, 2018)
Digital strategies have been formally recognized as a critical health systems strengthening strategy to help meet the Sustainable Development Goals and universal health coverage targets. This landscaping collection reviews multiple possible approaches across health system pillars, from digital referrals to decision support systems, identifying key knowledge gaps across these domains and recognizing the growth needed in the field to realize its full potential.